Time Trends and Geographic Variation in Use of Minimally Invasive Breast Biopsy - Zimmermann, Christopher J. (2013)
BACKGROUND: Current guidelines recommend minimally invasive breast biopsy (MIBB) as the “gold standard” for the diagnosis of breast lesions. The purpose of this study was to describe geographic patterns and time trends in the use of MIBB in Texas. METHODS: We used 100% Texas Medicare claims data (2000–2008) to identify women ≥66 years who underwent breast biopsy. Biopsies were classified as open or minimally invasive (MIBB). Time trends, racial/ethnic variation, and geographic variation in the use of biopsy techniques were examined. RESULTS: A total of 87,165 breast biopsies were performed on 75,518 breast masses in 67,582 women. 65.8% of the initial biopsies were MIBB. Radiologists performed 70.3% and surgeons 26.2% of MIBB. Surgeons performed 94.2% of open biopsies. Hispanic women were less likely to undergo MIBB (55.9%) compared to white (66.6%) and black (68.9%) women (p<0.0001). Women undergoing MIBB were also more likely to live in metropolitan areas and have higher income and educational levels (p<0.0001). The rate of MIBB increased from 44.4% in 2001 to 79.1% in 2008 (p<0.0001). There are clear geographic patterns in MIBB use with highest use near major cities. While rates are increasing overall, rates of improvement in the use of MIBB vary significantly across geographic regions and remain persistently low in more rural areas. CONCLUSION: Despite an increase in the use of MIBB over time, MIBB use was consistently lower than recommended. We must identify specific barriers in rural areas to effectively change practice and achieve the statewide goal of 90% MIBB.